Efficacy of Kinesiotape to Improve Upper-Extremity Function in Children and Adolescents with Cerebral Palsy: A Systematic Review - Victoria Calvo-Fuente; Concepción Soto-Vidal; Ana Ramón-Corcoba; Ester Cerezo-Téllez; Yolanda Pérez-Martín; Soraya Pacheco- (MDPI AG, 2024)
Background: Cerebral palsy (CP) is one of the primary causes of physical disabilities in children that affects posture and movement. Upper-extremity (UE) function is frequently impaired, which may result in activity and participation limitations in people with CP. The use of kinesiotape (KT) has increased in the treatment of CP for various purposes. The aim of this systematic review was to assess the efficacy of KT for improving UE function in children and adolescents with CP. Methods: The literature search was carried out in PubMed, Cochrane, PEDro, Web of Science and SCOPUS databases. The methodological quality was analyzed with the PEDro scale. Review Manager (RevMan 5.4.1) was used for data extraction and risk of bias assessment. Results: A total of five randomized clinical trials were included. The use of KT showed improvement in UE functionality in three studies, with significant outcomes for range of motion (ROM) (three studies), fine motor skills (two studies), grip strength (one study) and manual dexterity (one study). Moreover, it also showed significant improvements in spasticity and gross motor function (one study). Overall, methodological quality was moderate, and the risk of bias was high in the domains related to blinding. Conclusion: The use of KT showed improvement in UE function in children and adolescents with CP. However, further research is needed to reinforce the conclusions on the efficacy of KT as a therapeutic tool.